Enhancing building construction projects delivery: Identifying critical success factors - Igbokwe, Guy; Ubani, Emmanuel; Okorocha, Kevin; Anyanwu, Columbus (Journal of Commerce, Management, and Tourism Studies, 2025)
The study is aimed at development of critical success factors for enhance building construction projects delivery using South East Nigeria as a study area. The problem of the study is failure to identify and prioritize critical success factors (CSFs). The specific objective is to identify and evaluate the critical success factors (CSFs). The basic sources of data collected for the study are secondary data which include brainstorming, published relevant information and primary data gotten by the respondents/professionals. The researcher reviewed related literature which enabled him to develop a questionnaire. Data was collected through email, questionnaire and interview approach which was distributed among the stakeholders. Analysis of data was carried out with Descriptive Statistics and Structural Equation Modeling (SEM). The results and finding shows that design, pre-construction, construction, post construction phase have an influence on constructability. The researcher concluded that lack of quality control and client dissatisfaction have an influence on constructability. Early involvement of contractors in the design stage and improving the spirit of teamwork have a direct impact on improving constructability and reducing duplication.